The Role of Public Relation at Universitas Negeri Semarang for Implementation of Public Information Disclosure Policy - Ledi Diyanasari; Intan Permata Hapsari; Darmoyo Darmoyo; Imam Adi Nugroho (Universitas Negeri Semarang, 2023)
The purpose of this study is to find out how big the role of public relations at Universitas Negeri Semarang is in implementing public information disclosure policies (Law No. 14 of 2008) and what strategies are used by public relations in its role as a communicator , relationship builder , forming a good image of the organization as well as a backup management to present information to the public. Disclosure of public information is one of the obligations that must be carried out by Public Agencies to maintain public confidence in the performance of programs and budgets implemented. Universitas Negeri Semarang (UNNES) is a public agency that through the Public Relations Unit (Humas) provides information and documentation services in accordance with public requests. The research method used is qualitative description by making data analysis from data collection carried out by observation, interviews and documentation of the Public Relations unit at UNNES. The research results obtained illustrate that the Public Relations Unit has carried out its role quite well as a communicator , builder of relations with internal and external parties and as a positive image creator for UNNES through media that has been designated as a means of communication between UNNES and the public. The strategy used by Public Relations in its role of providing information services by utilizing social media is more accessible to the public. The constraints that occur are not optimal utilization of the website http://ppid.unnes.ac.id which provides public information in accordance with Law 14 of 2008. Henceforth Public Relations must be able to optimize human resources and infrastructure in order to provide information and documentation services openly to the public